THE ROLE OF THE PPAT NOTARY IN PROVIDING PRIVATE SERVICES TO LAND FORMER TRADITIONAL OWNERSHIP - Indra, Indra (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
After the UUPA came into effect, all land rights throughout Indonesia were subject to the land law regulated by the UUPA. In fact, in society there are still rights to land from customary law, so a conversion was carried out from the customary law atmosphere to UUPA. For legal certainty of land rights so that the Head of the National Land Agency issues a special policy regarding customary land registration procedures, the aim of this research is to analyze the certification process for customary land rights and analyze the legal protection of customary land after the certificate is mandatory. The type of research used is normative juridical regarding Law Number 5 of 1960 and Government Regulations in implementing the Conversion of Land Registration for Former Customary Ownership Rights to Land Rights Certificates using a statutory regulatory approach and a conceptual approach. The results of this research are With the enactment of the UUPA, then All land must be subject to the UUPA as the second legal unification regarding land. For customary land rights to become subject to the UUPA, conversion is carried out. For customary land which does not have written or unwritten evidence where the conversion is carried out by the Adjudication Registration Committee acting on behalf of the Head of the National Land Office, the process is carried out by affirmation of rights, while for customary land rights which do not have evidence it is carried out by a process of recognition of rights.